Maxillary Intercanine Width in a South Sumatran Population: Implications for Maxillofacial Reconstruction - Mufida Muzakkie; Lawrencia Toline; SNA Ratna Sari Devi; Ziske Maritska (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2024)
Introduction: The maxilla is a crucial bone in the facial skeleton, contributing significantly to both aesthetics and function. Understanding the morphometric variations of the maxilla, particularly the intercanine width (ICW), is vital for successful maxillofacial reconstruction procedures. This study aimed to investigate the ICW in a South Sumatran population, considering its implications for reconstructive surgeries. Methods: This retrospective study analyzed computed tomography (CT) scans of 96 adult patients (60 males, 36 females) from South Sumatra. The ICW was measured using 3D reconstruction software, and the data were analyzed for gender-based differences. The findings were compared with existing literature to understand regional variations in maxillary morphology. Results: The mean ICW for males was 3.58 ± 0.27 cm and for females was 3.44 ± 0.18 cm. Males exhibited a significantly larger ICW than females (p < 0.05). These findings are consistent with previous studies indicating sexual dimorphism in maxillary morphology. Conclusion: This study provides valuable data on maxillary intercanine width in a South Sumatran population. The observed gender-based differences highlight the importance of considering patient demographics in maxillofacial reconstruction. This information can aid surgeons in achieving optimal functional and aesthetic outcomes.